Zrównoważony rozwój regionalny - Świąder, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The concept of sustainable regional development is a relatively new issue, which is the main object of traditional regional policy. According to the idea of sustainable development, regional equality development should be concentrated on sustainable development, prudent management and protection of nature and cultural heritage. The strategic regional document should take into account these guidelines, particularly sustainable development of the spatial structure. The main aspect of this study was to show the level of implementation of the idea of sustainable development at the regional level, with particular emphasis on spatial policy of the country. Poland is still at the stage of introducing the necessary changes that will improve the quality of the living space. The regional strategic and planning document disregards and does not respect the principles of sustainable development. This attitude is apposed to the European approach where the aim of spatial development policies is to work toward a balanced sustainable development.
Keywords: region; polityka regionalna; zrównoważony rozwój; dokumenty strategiczne; polityka przestrzenna